THE TOURISM DEVELOPMENT THROUGH CBT IN PONGGOK VILLAGE - Ade Pugara; Brian Pradana (Program Studi Perencanaan Wilayah dan Kota, Fakultas Teknik, Universitas Semarang, 2021)
Community-based tourism (CBT) is the most popular approaches in tourism development. The main principle of CBT is giving access to the community in tourism management and development equally. Furthermore, the main goal of CBT is creating community empowerment in tourism. Therefore, the community has competitive advantages to enhance tourism quality and keep it sustain (Hausler and Strasdas, 2003)..In 2015 Ponggok received the village Annual Budget (Dana Desa) from the central government. Through that budget, the local government establish the Village Company (BUMDes), which is focusing on tourism development. In the tourism development, Ponggok attempt to use Pongok water springs as the main tourist attraction.. Based on these facts, this research wants to examine